Activation of SO2 with [(η5‐C5Me5)2Ln(THF)2] (Ln=Eu, Yb) Leading to Dithionite and Sulfinate Complexes. Issue 42 (4th September 2014) - Klementyeva, Svetlana V.; Gamer, Michael T.; Schmidt, Anna‐Corina; Meyer, Karsten; Konchenko, Sergey N.; Roesky, Peter W.
Abstract: The reaction of decamethylytterbocene [(η 5 ‐C5 Me5 )2 Yb(THF)2 ] with SO2 at low temperature gave two new compounds, namely, the Yb III dithionite/sulfinate complex [{(η 5 ‐C5 Me5 )2 Yb(μ3, 1κ 2 O 1, 3, 2κ 3 O 2, 2′, 4 ‐S2 O4 )}2 {(η 5 ‐C5 Me5 )Yb(μ, 1κO, 2κO′‐C5 Me5 SO2 )}2 ] (1 ) and the Yb III dithionite complex [{(η 5 ‐C5 Me5 )2 Yb}2 (μ, 1κ 2 O 1, 3, 2κ 2 O 2, 4 ‐S2 O4 )] (2 ). After extraction of1, the mixture was heated to give the dinuclear tetrasulfinate complex [{(η 5 ‐C5 Me5 )Yb}2 (μ, κO, κO'‐C5 Me5 SO2 )4 ] (3 a ). In contrast, from the reaction of [(η 5 ‐C5 Me5 )2 Eu(THF)2 ] with SO2 only the tetrasulfinate complex [{(η 5 ‐C5 Me5 )Eu}2 (μ, κO, κO'‐C5 Me5 SO2 )4 ] (3 b ) was isolated. Two major reaction pathways were observed: 1) reductive coupling of two SO2 molecules to form the dithionite anion S2 O4 2− ; and 2) nucleophilic attack of one metallocene C5 Me5 ligand on the sulfur atom of SO2 . The compounds presented are the first dithionite and sulfinate complexes of the f‐elements. Abstract : Reduction chemistry : The reaction of decamethylytterbocene [(η 5 ‐C5 Me5 )2 Yb(THF)2 ] with SO2 resulted in the Yb III dithionite complex [{(η 5 ‐C5 Me5 )2 Yb}2 (μ, 1κ 2 O, 2κ 2 O‐S2 O4 )] and the Yb III dithionite/sulfinate complex [{(η 5 ‐C5 Me5 )2 Yb(μ3, 1κ 2 O, 2κ 3 O‐S2 O4 )}2 {(η 5 ‐C5 Me5 )Yb(μ, 1κO, 2κO′‐C5 Me5 SO2 )}2 ]. Also, the dinuclear tetrasulfinate complexes [{(η 5 ‐C5 Me5 )Ln}2 (μ, κO, κO′‐C5 Me5 SO2 )4 ] (Ln=Eu, Yb) were isolated.